Optimization of the Process for Extracting Polysaccharides from Sargassum fusiforme Using Combined Enzymes and Analysis of Its Hypolipidemic Activity - Wenkai LIU; Dan OUYANG; Yangli XU; Laijin SU (Shipin gongye ke-ji)
To investigate the effect of the combination of pectinase and neutral protease on the extraction rate of polysaccharides and the hypolipidemic activity of polysaccharide products from Sargassum fusiforme, the preparation of Sargassum fusiforme polysaccharides (SFP) was optimaized by response surface methodology. The polysaccharide products were separated and purified by a purification instrument, of which the physicochemical properties were analysed by scanning electron microscope, Fourier transform infrared spectroscopy and high performance liquid chromatography. Finally, the hypolipidemic ability of SFP was evaluated in vitro using bile acid salt binding capacity and pancreatic lipase activity inhibition assays as well as in vivo by constructing an in vivo zebrafish hyperlipidemia model, respectively. Results showed that the optimal conditions for SFP preparation with the combined enzymatic method were determined: 4:1 ratio of pectinase to neutral protease, pH5.5, temperature 50 ℃, enzyme addition rate of 2%, and a solvent-to-material ratio of 25:1. Four SFP fractions were obtained by isolation and purification, among which SFP-4 was identified to effectively bind bile salts (EC50=0.3524 mg/mL) and inhibit pancreatic lipase activity (IC50=0.3568 mg/mL), with the best lipid-lowering activity. Further investigation of the physicochemical properties of SFP-4 revealed that it was composed of seven monosaccharides, including fucose, galactose, and glucuronic acid, and was characterized by a pore structure and the structure of sulfate polysaccharides. At a concentration of 500 μg/mL, lipid accumulation was significantly reduced in zebrafish (P<0.01), with the expression of fatty acid synthesis-related genes (mttp, pparg, and fasn) downregulated, while lipolysis-related genes (pparab and acaca) were upregulated. A comparable lipid-lowering effect to simvastatin was observed. In conclusion, the combined enzyme method could effectively improve the yield of SFP, and the polysaccharide products were demonstrated to possess significant hypolipidemic activity. This study provides a theoretical support for the development and utilization of the hypolipidemic function of Sargassum fusiforme polysaccharides.